International Posture and Intercultural Awareness: A Survey Study of Indonesian L2 Learners of English - Subekti, Adaninggar Septi; Andriyanti, Erna; Basikin, Basikin (Register Journal, 2024)
This study intended to investigate International Posture and Intercultural Awareness of Indonesian L2 learners of English who studied at English Language departments. It also sought to investigate the extent to which learners' International Posture influenced their Intercultural Awareness. It was conducted to fill the gap in the literature on the scarcity of studies on International Posture and Intercultural Awareness in Indonesia despite the likelihood of communication prospects in English with international people. To this end, it involved 73 participants studying in English Language Education departments at two universities in Java, Indonesia, in a survey. Through descriptive statistics on SPSS, the study found a quite high level of Intergroup Approach-Avoidance Tendencies (IAAT), the first dimension of International Posture. It also found a moderate-high level of Interest in International Vocation and Activities (IIVA), the second dimension of International Posture. Furthermore, the participants’ awareness of their own cultures and those of others was generally high though some of the participants' awareness of specific aspects of other cultures was reported to be low. Using multiple regression, the study found that generally, the participants’ International Posture significantly influenced their Intercultural Awareness, accounting for 22.3% of the total variance in Intercultural Awareness. However, from the beta coefficient analysis, it was found that only the participants’ IAAT significantly influenced their Intercultural Awareness in a positive direction. Their IIVA did not significantly influence it. The findings highlighted the need to nurture second/foreign language (L2) learners’ International Posture and conduct further investigation on the possible impacts of learners’ International Posture on learners’ ICC in general.